2010
DOI: 10.4161/gmic.1.5.13052
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloridirects tolerogenic programming of dendritic cells

Abstract: 3 Gastric CD103 + dendritic cells, which are known to induce mucosal regulatory T cells, were also increased in number, raising the question whether H. pylori infection induces a regulatory T cell-skewed response by way of a bacteria-dendritic cell interaction. In fact, bone marrow-derived dendritic cells underwent tolerogenic programming, skewing the balance between effector and regulatory T cell responses towards regulatory T cell differentiation in a transforming growth factor-β-and interleukin-10-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…It has become clear that hosts that mount a strong proinflammatory response are more likely to develop severe complications of disease, such as peptic ulcers or neoplasia (17), although the factors that determine which hosts will develop such responses remain unclear. In fact, the most recent evidence suggests that in humans, the primary response to infection is actually immunoregulatory (18)(19)(20)(21)(22). This finding supports many years of animal research indicating that suppression of regulatory responses is necessary for induction of severe disease (11,(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…It has become clear that hosts that mount a strong proinflammatory response are more likely to develop severe complications of disease, such as peptic ulcers or neoplasia (17), although the factors that determine which hosts will develop such responses remain unclear. In fact, the most recent evidence suggests that in humans, the primary response to infection is actually immunoregulatory (18)(19)(20)(21)(22). This finding supports many years of animal research indicating that suppression of regulatory responses is necessary for induction of severe disease (11,(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 52%
“…In fact, some have suggested that the principle response of normal hosts to infection is regulatory rather than proinflammatory and is mediated by Treg (17,21,22). We hypothesized that the exacerbated gastritis described in CD4 cell recipient mice compared to C57BL/6 mice (described above and in references 11, 23, and 24) may be attributable to the failure of Treg to engraft in the recipients.…”
Section: Gastritis Is Exacerbated In the Absence Of Treg Several Recmentioning
confidence: 93%
See 1 more Smart Citation
“…Specifically, H. pylori can trigger a reprogramming of dendritic cells (DC) by downregulating major histocompatibility complex II (MHC-II) and inducing interleukin-10 (IL-10) and inhibiting IL-12 secretion, thereby inducing H. pylori-specific Treg cells (16)(17)(18). B cells also play a regulatory role by promoting IL-10 production in cocultured CD4 ϩ cells and subsequent conversion into a T T lymphocytes were found in the gastric epithelium and lamina propria (LP) of H. pylori-infected children with grade I to III gastritis (22, 23).…”
mentioning
confidence: 99%
“…Similar to humans, the animal models of H. pylori infection are characterized by the induction of mixed CD4+ T cell responses mediated by Th1, Th17, and regulatory T cell (Treg) subsets, which also fail to eradicate the bacterium. 19 In recent years data from human clinical studies emphasize the potential relevance of another T cell subset, the CD8+ cytotoxic T lymphocytes, in the context of the immune responses to H. pylori. However, the development of CD8+ T cell responses has barely been reported in studies employing mouse or gerbil models of infection.…”
Section: Immune Response To Helicobacter Pylorimentioning
confidence: 99%